INCREASING STUDENTS’ READING COMPREHENSION THROUGH COGNITIVE STRATEGIES OF SENIOR HIGH SCHOOL OF SIDENRENG RAPPANG REGENCY - Elihami Elihami; Ismail Ismail (Universitas Muhammadiyah Enrekang, 2017)
This research is a quasi-experimental research at the objective of finding the increasing student’s reading comprehension achievement through the cognitive strategies (rehearsal, organization, and elaboration) and to what extent these cognitive strategies influences the student’s reading comprehension achievement. The subject of the research was Senior High School of Sidenreng Rappang regency consisting of 50 respondents into two classes from 11 schools of Sidenreng Rappang; each class consisted of 25 respondents, one class a control and another class as the tentative one. The data were collected through the reading comprehension test in pretest and posttest and the observation checklist during the teaching and learning process. The test consisted 0f 45 items of test from three kinds (news item, descriptive, and narrative text). The observation checklist consisted of four statements for rehearsal strategies, three statements for organization strategies, and one statement for elaboration strategy. The research findings showed that the students’ reading comprehension increased for both groups from pretest to posttest. The experimental group was higher than the control one (60.6 > 50.1) and the t-test was greater than the P-Value (0.05 > 0.007) which means that there was a significant difference after giving treatment to the experimental group. The application of cognitive strategies also influenced positively to the increasing students’ reading comprehension achievement. So, it was concluded that the use of cognitive strategies (rehearsal, organization, and elaboration) is useful to increase students’ reading comprehension in teaching and learning words.